The educational burden of ADHD: Evidence from student achievement test scores - Bernhard C. Dannemann; Erkan Gören (University of Oldenburg, Department of Economics, 2018)
This paper hypothesizes and empirically establishes the educational burden of the ADHD-related behavioral symptoms inattention and/or hyperactivity-impulsivity on aggregate cognitive achievement outcomes. We use a novel compilation of the 2- and 7-repeat allele variants of the human DRD4 exon III gene that candidate gene association studies have identified as an important biomarker in the etiology of childhood ADHD. The main results show a negative and statistically significant association between aggregate international student achievement test scores and the DRD4 exon III 2- and 7-repeat allele frequency measure in a cross-section of 81 countries. This finding is robust to the inclusion of additional country-specific historical, cultural, socioeconomic, biogeographic, health-related, educational, genetic, and diversity factors. Additional estimates suggest the predictive power of the country-level DRD4 exon III 2- and 7-repeat allele frequency measure on cross-country differences of estimated ADHD prevalence rates, confirming the reliability of the proposed biomarker for the measurement of ADHD-related behavioral symptoms in the general population.
Keywords: E70; I10; I20; J24; 330; Human Capital; Cognitive Ability; Cognitive Skills; International Student Achievement Tests; Education Production Function; ADHD; DRD4 Exon III; Genetic Diversity